The Impact of Organizational Change on Employees’ Performance: A survey of Nigerian Deposit Money Banks - Adekunle , Faloye, O. D.; Oladimeji, S. B.; Adekunle , Kazeem, Y. K. (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2020)
This study investigated how organisational change affects employees’ performance in the Nigerian banking industry. This paper was based on an empirical investigation of eighteen banks operating in Ondo State. Data were collected through a survey questionnaire from 254 respondents purposively selected for the study and were analysed using the regression model. The results revealed that the organisational change constructs covered in this study had a significant influence on employees’ innovative performance, productivity, and customer service performance. This study concluded that since organisational change dimensions would play a significant role in providing information to predict employee’s performance, there should be re-orientation for employees mostly the older ones about the presence and need for change in the Nigerian banking sector through continuous training, workshops, and group discussions thereby reducing the fear of the unknown.